In-Vivo Acute Dermal Irritation Study Of Desonide-Curcumin Niosomal Gel: An Experimental Approachs - Waman, Rahul; Gupta, Ravikant; Kumar Jain, Sachin; Vengurlekar, Sudha (Journal of Neonatal Surgery, 2025)
Topical niosomal gels have gained considerable attention for enhancing localized drug delivery and reducing systemic side effects. Desonide, a corticosteroid, and curcumin, a natural anti-inflammatory compound, are both recognized for their therapeutic potential in treating skin inflammation. This study aimed to evaluate the dermal irritation potential of a Curcumin–Desonideniosomal gel in Wistar rats using OECD guideline 404. Thirty Wistar albino rats were randomly divided into five groups (n = 6 each): Group I (Normal Control), Group II (Positive Control with 0.8% formaldehyde), Group III (Placebo gel base), Group IV (Curcumin–Desonideniosomal gel), and Group V (Marketed Diclofenacniosomal gel). Skin reactions were observed and scored at 24, 48, and 72 hours post-application using the Draize scoring system for erythema, edema, and swelling. The results demonstrated no skin reactions in the normal control group, while the formaldehyde-treated group showed severe irritation with high scores across all parameters. The placebo group exhibited only very slight irritation at 24 hours that resolved by 48 hours. The Curcumin–Desonideniosomal gel group showed minimal erythema at 24 hours, with no edema or swelling, and no signs of irritation at 48 and 72 hours. The marketed niosomal gel also showed minimal erythema with no other adverse effects. These findings confirm that the Curcumin–Desonideniosomal gel is well-tolerated and non-irritant, supporting its potential as a safe and effective topical formulation for anti-inflammatory therapy.